(untitled) (INNOVATIVE ECONOMY, 2020)
Balaniuk I.F., Maksymiuk M.M. SYSTEMIZATION AND SUBSTANTIATION OF INDICATORS OF ASSESSMENT METHODS OF ECONOMIC SECURITY LEVEL AT AGRICULTURAL ENTERPRISES Purpose. Systematization and generalization of existing scientific approaches and methods of studying and evaluating economic security at the micro level in order to substantiate the most actual and practically significant indicators of activity of enterprises in the field of agriculture. Methodology of research. To achieve the objectives, used dialectical methods, a systematic approach to taking into account the peculiarities of agricultural enterprises, generalization of indicators reflecting the efficiency of various economic processes and other methods of scientific research are used. Findings. It has been found that most of the modern methods of assessing the level of economic security, despite their similarity, differ in the peculiarities of the interpretation of economic security, although they use similar economic indices-indicators. On the basis of the proposed (developed) definition of the economic security of the enterprise, three groups of indicators have been presented and justified, which should be used to assess the economic security of agricultural enterprises. For each component of economic security (the state of the enterprise as a production system, the level of efficiency of activities and the level of protection against potential threats), a group of indicators describing specific economic processes of the enterprise, taking into account the specifics of the agricultural sector. Originality. On the basis of systematization and analysis of scientific researches on the assessment of the level of economic security, their weaknesses have been identified and taken into account when forming and substantiating the usage of a number of specific activity indicators. The specificity of agricultural enterprises work has been taken into account, and a number of indicates indicators, which are specific for agricultural enterprises, have been proposed. Practical value. The obtained results are distinguished by their practical orientation and are based on leading scholars` research. Critical analysis of a number of positions allowed to highlight the most practically significant indicators of activity of agricultural enterprises in order to allow further practical application of the results. Key words: economic security; agricultural enterprises; assessment of economic security; efficiency; prevention of bankruptcy; indicators of enterprise activity; protection against economic threats; peculiarities of agribusiness activity.